FUNGSI TRADISI ALEK BAKAJANG DALAM MEMPERERAT INTEGRASI SOSIAL MASYARAKAT DI KENEGARIAN GUNUANG MALINTANG KECAMATAN PANGKALAN KOTO BARU KABUPATEN 50 KOTA SUMATRA BARAT - Hafizatul Ismi; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Bakajang is one Gunuang Malintang Nagari tradition that has been passed down through generations of ancestors. Kajang is a means of transportation in the past used by niniak mamak 4 parts of the temple toward Nagari Gunuang Barelang Malintang that crosses the river waters Trunk Mahat. The purpose of this is Alek bakajang increase the friendship between the village children, ninik mamak, clergy and government, with the aim of strengthening unity, preserving indigenous cultural villages, village youth evokes creativity, and a means of conveying information customs, religion, laws and government information and villages increase the income of the people. Participants and actors bakajang Alek is young, ninik mamak, teachers, administration Nagari, community leaders, PKK and Bundo Kanduang, nomads and villagers' donors and Mount Malintang. Being the problem is: what are the procedures for Alek Bakajang Tradition? and how to function in the tradition of Alek Bakajang Mayarakatnya memperertat Social Integration? This study aims to describe the procedures for Alek Bakajang tradition and to determine the function of tradition Alek Bakajang in strengthening social integration. This research is a simple random sampling with a qualitative descriptive approach. Data needs include primary data obtained through filling koesioner results, interviews, and pegamatan and secondary data obtained from the Office of the District 50 City and monograph Kenegarian Gunuang Malintang. Total population of 1060 people and the sample was 53. From the results of this research is that Alek Bakajang Tradition can deepen social integration in society, as the first strengthen the unity and integrity of the community, it is seen from the settlement of the conflict in Kenegarian Gunuang Malintang. both strengthen the relationship silaturrahmi, silaturrahmi seen from this study is that people visit each other Malintang Gunuang during Eid and visit each other and when one of the members of the community experiencing disaster or misfortune. The third is to improve cooperation in society Gunuang Malintang, visible forms of cooperation is mutual and the Mutual Joint Venture (Joint Venture).Keywords: Alek Bakajang Tradition, Social Integration